Safety and efficacy of the FAKHRAVAC compared with BBIBP-Corv2 against SARS-CoV-2 in adults: a non-inferiority multi-center trial - Masoud Solaymani-Dodaran; Pouria Basiri; Milad Moradi; Kimiya Gohari; Ali Sheidaei; Mohammadreza Ahi; Farzad Ghafoori Naeeni; Akram Ansarifar; Zahra Rahimi; Fatemeh Gholami; Ahmad Karimi Rahjerdi; Ramin Hamidi Farahani; et al. (Virology Journal, 2023)
Abstract Background We compared Fakhravac and BBIBP-Corv2 vaccines in a phase III trial. Method We conducted a multicenter, parallel-group, active-control, non-inferiority clinical trial with pragmatic considerations assessing the safety and efficacy of Fakhravac and BBIBP-Corv2 vaccines. We started with two randomized double-blind arms and added two non-randomized open-label arms (based on participant preference) because of slow recruitment. The adult population received 0.5 ml (10 µg per dose) intramuscular injections of Fakhravac or BBIBP-Corv-2 vaccines 21 days apart. The primary outcome was the occurrence of PCR-positive symptomatic Covid-19 disease 14 days or more after the second injection. A 10% non-inferiority margin to the reported 72.8% efficacy of BBIBP-Corv2 was assumed. Cox proportional hazard modeling was used to estimate hazard ratios and their 95% confidence intervals. Result We enrolled 24,056 adults in four groups (randomized-Fakhravac: 824, randomized-BBIBP-Corv2: 832; Non-randomized-Fakhravac: 19,429, Non-randomized-BBIBP-Corv2: 2971). All observed local and systemic adverse reactions were generally self-limited and resolved completely. We observed similar Serious Adverse Event (SAE) rates in the BBIBP-Corv2 (2.57, 95% CI 1.33–4.49) and Fakhravac (2.25, 95% CI 1.72–2.89) groups; none of which were related to the vaccines received. We recorded 9815 Medically Attendant Adverse Events (MAAE), 736 of which were categorized as somehow related. The rate of related MAAE in the Fakhravac was similar to the BBIBP-Corv2 groups (0.31 and 0.26 per 1000 person-day) in the randomized and considerably higher (0.24 and 0.07 per 1000 person-day) in the non-randomized arms. We observed 129 (35% of the 365 required by target sample size) events of PCR + symptomatic Covid-19 during four months of active follow-up in the randomized arm, demonstrating that those receiving the Fakhravac vaccine were significantly less likely (HR = 0.69; 95% CI 0.49–0.98) to be diagnosed with PCR + symptomatic Covid-19 compared with those receiving BBIBP-Corv2 vaccine. After adjusting for type I error using the O’Brien Fleming method, the Fakhravac vaccine was non-inferior to the BBIBP-Corv2 (assuming a 10% non-inferiority margin to the reported 72.8% BBIBP-Corv2 vaccine efficacy; HR < 1.35) (One-way test: HR = 0.66; 99.8% CI 0.38–1.15). In the non-randomized arm, the results were inconclusive (HR = 1.23; 95% CI 0.96–1.61). We observed 5 cases of hospitalized Covid-19 in the randomized arm, none of which occurred in the Fakhravac vaccine group. Those receiving the Fakhravac vaccine were four times less likely to go to the hospital because of a Covid-19 diagnosis (HR = 0.24; 95% CI 0.10–0.60). The vaccine efficacy of the Fakhravac vaccine is estimated to be 81.5% (95% CI 81–82.4%). Conclusion Fakhravac inactivated SARS-CoV-2 vaccine has comparable safety and efficacy to the BBIBP-Corv2 vaccine. Trial registration This study was registered with the Iranian Registry of Clinical Trials ( www.irct.ir : IRCT20210206050259N3).